Ambivalent and heavy burdened wanderers on a road less travelled: a meta-ethnography on end-of-life care experiences among family caregivers in rural areas - Elisabet Breivik; Bente Ervik; Gabriele Kitzmüller (BMC Health Services Research)
Abstract Background As the population ages, more people will be diagnosed with cancer, and they will live longer due to receiving better treatment and optimized palliative care. Family members will be expected to take on more responsibilities related to providing palliative care at home. Several countries have expressed their vision of making home death an option, but such a vision can be more challenging in rural areas. There is a lack of synthesized research providing an in-depth understanding of rural family caregiving for people with cancer at the end of life. Thus, the purpose of this study was to synthesize and reinterpret the findings from qualitative research on rural family caregivers of adult cancer patients at the end of life. Methods We conducted a meta-ethnography following Noblit and Hare’s approach. A systematic literature search of four databases and extensive manual searches were completed in April 2022. The final sample included twelve studies from six different countries published in 2011–2022. Results Based on the translation and synthesis of the included studies, four themes were developed (1) providing family care at the end of life in rural areas—a challenging endeavour; (2) the heavy responsibility of rural caregiving—a lonesome experience; (3) working on and behind the scenes; and (4) the strong and weak spots of community connectedness in rural areas. An overarching metaphor, namely, “ambivalent and heavy burdened wanderers on a road less travelled”, provides a deeper understanding of the meaning of rural family caregiving at the end of life. Conclusions This study provides valuable insights into end-of-life cancer care for rural families on four continents. It is crucial to prepare family caregivers for the demanding role of palliative caregiving in rural areas. To address the long distances and poor access related to specialized health care services, outpatient palliative teams tailored to the families’ individual needs should be provided. In addition, more telehealth services, palliative units, or beds in local nursing facilities may reduce the number of exhausting trips that need to be made by caregivers and patients. Healthcare workers in rural areas need further education in palliative care. Trial registration The study was registered in PROSPERO.